Proceedings of the 7th Annual International Conference on Mobile Computing and Networking 2001
DOI: 10.1145/381677.381697
|View full text |Cite
|
Sign up to set email alerts
|

Distributed multi-hop scheduling and medium access with delay and throughput constraints

Abstract: Providing quality of service in random access multi-hop wireless networks requires support from both medium access and packet scheduling algorithms. However, due to the distributed nature of ad hoc networks, nodes may not be able to determine the next packet that would be transmitted in a (hypothetical) centralized and ideal dynamic priority scheduler. In this paper, we develop two mechanisms for QoS communication in multi-hop wireless networks. First, we devise distributed priority scheduling, a technique tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(133 citation statements)
references
References 19 publications
1
131
0
Order By: Relevance
“…11 also demonstrates that when node density is sufficiently high (M = 5 & corresponding node density > 12.78), statistically the pseudoproblem rarely happens (< 0.2 percent) when the localization error below half radio range. This theoretical analysis is consistent with our simulation result in [11].…”
Section: Pseudovoid Problemsupporting
confidence: 93%
See 2 more Smart Citations
“…11 also demonstrates that when node density is sufficiently high (M = 5 & corresponding node density > 12.78), statistically the pseudoproblem rarely happens (< 0.2 percent) when the localization error below half radio range. This theoretical analysis is consistent with our simulation result in [11].…”
Section: Pseudovoid Problemsupporting
confidence: 93%
“…RAP [16] uses velocity monotonic scheduling to prioritize real-time traffic and enforces such prioritization through a differentiated MAC Layer. Kanodia et al [11] proposed a service differentiation for delaysensitive traffic by prioritizing 802.11. Woo and Culler [21] proposed an adaptive MAC layer rate control to achieve fairness among nodes with different distances to the base station.…”
Section: State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…Medium access and packet scheduling algorithm must select and transmit packets in accordance with QOS requirements Distributed Dynamic Priority scheduling provide packet transmission in multihop wireless network with high fraction of Quality of Service [10].…”
Section: Related Workmentioning
confidence: 99%
“…Their results show that in certain scenarios significant improvements in fairness can be achieved without sacrificing throughput. Protocols other than the IEEE 802.11 MAC scheme have also been proposed [10,11]. In [5] it is shown that intelligently tuning the parameters used in TCP and the IEEE 802.11 protocols improves performance.…”
Section: Introductionmentioning
confidence: 99%